2015
DOI: 10.1055/s-0035-1546082
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Investigation of the Piperineʼs Male Contraceptive Effect: Docking and Molecular Dynamics Simulation Studies in Androgen-Binding Protein and Androgen Receptor

Abstract: Understanding the molecular mechanism of action of traditional medicines is an important step towards developing marketable drugs from them. Piperine, an active constituent present in the Piper species, is used extensively in Ayurvedic medicines (practiced on the Indian subcontinent). Among others, piperine is known to possess a male contraceptive effect; however, the molecular mechanism of action for this effect is not very clear. In this regard, detailed docking and molecular dynamics simulation studies of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Chinta G, Periyasamy L. Anti-spermatogenic Effect of Piperine … Drug Res 2016; 66: 420-426 methacin, isoniazid, ethambutol, phenobarbitone, phenytoin, dapsone and ciprofloxacin [27][28][29]. Based on the positive modulation of bioavailability properties of piperine on anti-tubercular drugs like isoniazid and rifampicin, synergistically active formulations are available for clinical use in India since 2009 [8]. More interestingly, a literature survey completed in 2006 also reported that, catpiperine from the species of Piper longum and Piper nigrum possess the male contraceptive properties [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinta G, Periyasamy L. Anti-spermatogenic Effect of Piperine … Drug Res 2016; 66: 420-426 methacin, isoniazid, ethambutol, phenobarbitone, phenytoin, dapsone and ciprofloxacin [27][28][29]. Based on the positive modulation of bioavailability properties of piperine on anti-tubercular drugs like isoniazid and rifampicin, synergistically active formulations are available for clinical use in India since 2009 [8]. More interestingly, a literature survey completed in 2006 also reported that, catpiperine from the species of Piper longum and Piper nigrum possess the male contraceptive properties [3].…”
Section: Discussionmentioning
confidence: 99%
“…Trikatu, an Ayurvedic formulation containing black pepper and long pep-per as its ingredients were utilized for inducing the menstruation in the process of abortion [7]. Piperine is an active constituent present in Piper nigrum(black pepper) and Piper longum (long pepper), and is responsible for the pungency of these herbs [8]. Animal studies proved the effectiveness of piperine in treating various disorders like cognitive difficulties and depression [9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Piperine is responsible for the pungency of both the herbs. [ 4 ] A formulation containing these two herbs as active ingredients was employed for inducing menstruation and as abortifacient in Indian traditional medicine. [ 5 ] Preclinical studies revealed the effectiveness of piperine in treating ailments such as neuronal difficulties and depression.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 25 26 ] Based on bioenhancing properties of piperine on antitubercular drugs such as isoniazid and rifampicin, synergistically acting formulations are available for clinical use in India since 2009. [ 4 ] A recent survey suggests that piperine is one among the 108 plant active constituents reported to have anti-fertility activity. [ 27 ] Furthermore, recent studies have proven the anti-fertility activity of piperine on male albino rats after 30 days of treatment.…”
Section: Introductionmentioning
confidence: 99%